(untitled) (Journal of the College of Education for Women, 2019)
This research, the author deals with a number of topics, including: What is interpretation?, the difference between exegesis and I interpretation of the Quran, the meaning of interpretation in the term, and the meaning of interpretation in the terminology of the people of interpretation, It deals with then, he demonstrates the interpretation and reasoning meanings of language, and the need of Muslims to interpret the Quran, and limitations of the use of interpretation and exegesis, On the interpretation of opinion and when it began, and the need of Muslims to explain, Finally he discusses the ways of interpretation, and the conditions to be provided in the interpreter.